Kinetics of Prilezhaev Epoxidation of Palm Olein - Vincent, Ivan (Universiti Teknologi PETRONAS, 2016)
The application of modified plant oils in industries is becoming increasingly attractive over recent years due to its availability from renewable resources. These chemically modified plant oils can be utilized as feedstock to make variety of industrial products. Epoxidized palm oil is recognized as one of the modified plant oils that has the commercial significance among many chemical modified plant oils available in the market. The epoxidized palm oils are generally produced via the method popularized by Prilezhaev where the unsaturated double bonds will be converted into epoxide rings. However, the common epoxidation process using the Prilezhaev method is highly exothermic and can easily lead to runaway reactions. Therefore, the study of kinetics is essential for the epoxidation process. Due to the complexity and safety of the epoxidation process, the study of the epoxidation of palm oil (RBD Palm Olein, POo) is crucial and need to be developed at laboratory scale before scaling-up to higher scales such as pilot or commercial plants.